Bacterial effect of hydrogen peroxide on urinary tract pathogens. - Schaeffer, A J (1980)
Bacterial contamination of urinary drainage bags is a frequent source of bladder bacteriuria in patients with indwelling catheters. Previous work demonstrated that the addition of 30 ml of 3% H2O2 prevented bacterial contamination of urinary drainage bags for up to 8 h in patients with urinary infections (greater than 10(5) colony-forming units per ml). Survival curves of a variety of organisms in filter-sterilized urine with various concentrations of H2O2 (0.6 to 0.01%) were constructed. Organisms with high cellular catalase activity (Staphylococcus aureus, Serratia marcescens, and Proteus mirabilis) required 30 to 60 min of exposure to 0.6% H2O2 for a reduction of 10(8) to less than 1 colony-forming unit per ml, whereas Escherichia coli, Streptococcus sp., and Pseudomonas sp. required only 15 min of exposure. The efficacy of H2O2 in urine was maintained despite exposure to room temperature for 5 days and reinoculation with bacterial suspensions. H2O2 is inexpensive and relatively nontoxic, and these data suggest that periodic instillation of H2O2 into urinary drainage bags may eliminate a source of bladder bacteriuria and environmental contamination.